Research on the energy efficiency of the multiphase nanosecond pulsed discharge system with TiO2 photocatalysis. Issue 1 (May 2021) - Che, Rui; Sun, Ming; Xu, Haiyang
Abstract: Energy efficiency of the system is always paid more attention in the research of the discharge plasma's application technology. Based on the project of ballast water treatment technology by multiphase nanosecond pulse discharge cooperated with photocatalysis, the nozzles-plate electrode was adopted, system energy and energy efficiency were investigated with different discharge factors and compared when the nozzles were coated with the titanium dioxide (TiO2 ) film or not. The results show that cooperating with the photocatalysis, pulsed discharge system power and energy efficiency were not significantly affected. Reactor power increases with the absolute value of the input high voltage and pulse repetition frequency and decreases with the distance between the nozzles and the plate. There are no obvious effects of the numbers of the nozzles and the air flow rate. Energy efficiency of the system increases with the absolute value of the input high voltage, firstly, then decreases. It changes inversely with the air flow rate. The energy efficiency of the system decreases with the pulsed repetition rate and the distance between the nozzles-plate. It was up to 25.7% with the input voltage of - 30 kV, and the air flow rate of 80 mL/min, pulse repetition frequency of 50 Hz and 6 nozzles- plate distance of 0.5 cm.